Air-Dried and Wet Fixation on Fine Needle Aspiration Biopsy (FNAB) Specimen - Fitri Nuroini; Zaldy Alfanda Hidayat; Tulus Ariyadi (Jurnal Teknologi Laboratorium, 2021)
Two fixation methods can affect the quality of cytological staining derived from fine-needle aspiration biopsy, but both fixation methods have drawbacks. Dry fixation can cause cell rupture, while wet fixation requires a longer time and costs more, so dry fixation is more often used. The purpose of this study was to compare the results of the Diff-Quick staining of cytological preparations that were fixed with the dry fixation method and the wet fixation method on FNAB samples. This study was an experimental study with 36 samples of cytology preparations from FNAB, divided into three groups, the control group, dry fixation group, and wet fixation group. Staining dry fixation preparations gave four poor results, five good preparations, and three very good preparations while staining wet fixation preparations gave 0 poor results, eight good preparations, and four very good preparations. This shows that the staining results of wet-fixed preparations tend to be of better quality and more consistent than the staining results of dry-fixed preparations. Even though statistically through the test Post-Hoc showed no difference, the quality of Diff-Quick staining of cytological preparations fixed by wet fixation method was better than dry fixation, so the wet fixation method was more recommended for cytological preparations than FNAB.